2020
DOI: 10.1093/eurheartj/suaa135
|View full text |Cite
|
Sign up to set email alerts
|

Lipoprotein(a) and PCSK9 inhibition: clinical evidence

Abstract: Compelling evidence has emerged from epidemiological and Mendelian randomization analyses relative to the causality of lipoprotein(a) [Lp(a)] in atherosclerotic cardiovascular diseases (ASCVD), being elevated Lp(a) a strong risk factor regardless of the reduction of LDL-C achieved by statins. So far, no specific available agent can lower Lp(a) to the extent required to achieve a cardiovascular (CV) benefit, i.e. approximately 100 mg/dL. The most recent outcomes trial FOURIER with evolocumab showed that a 25 nm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 20 publications
(23 reference statements)
0
17
0
Order By: Relevance
“…Proprotein convertase subtilisin/Kexin type 9 (PCSK9), an enzyme that is formed in the liver, has been described as a central player in cholesterol metabolism, particularly because PCSK9 stimulates the degradation of the LDL receptor and then leads to an increase in circulating LDL [ 75 ]. Inhibition of PCSK9 and its associated drastic reduction in circulating LDL suggests a promising treatment for patients with cardiovascular diseases [ 76 , 77 ]. In addition to lowering LDL, PCSK9 inhibitors were associated with a 15 to 30% reduction in Lp(a) plasma levels, which may benefit CAVD patients.…”
Section: The Effect Of Lipid-lowering Therapy In Aortic Stenosismentioning
confidence: 99%
“…Proprotein convertase subtilisin/Kexin type 9 (PCSK9), an enzyme that is formed in the liver, has been described as a central player in cholesterol metabolism, particularly because PCSK9 stimulates the degradation of the LDL receptor and then leads to an increase in circulating LDL [ 75 ]. Inhibition of PCSK9 and its associated drastic reduction in circulating LDL suggests a promising treatment for patients with cardiovascular diseases [ 76 , 77 ]. In addition to lowering LDL, PCSK9 inhibitors were associated with a 15 to 30% reduction in Lp(a) plasma levels, which may benefit CAVD patients.…”
Section: The Effect Of Lipid-lowering Therapy In Aortic Stenosismentioning
confidence: 99%
“…Available lipid-lowering therapies have little value for Lp(a) reduction. Aside from statins that could raise Lp(a) blood concentrations [68,69], PCSK9 inhibitors reduce Lp(a) levels by 25-30% [70] and there is evidence that reduction of Lp(a) elicited by these drugs might contribute to an improved prognosis in coronary disease patients [71]. Finally, for patients with progressive ASCVD and high plasma Lp(a), a possible approach sometimes used is lipoprotein apheresis [72].…”
Section: Lp(a)-novelties In the Era Of Rna-based Therapiesmentioning
confidence: 99%
“…93 The 25 nmol/L (12 mg/dL) reduction in Lp(a) corresponded to a 15% reduction in CVD events. 94 Data from 4 Phase 3 trials with evolucumab comprising 895 patients showed heterogeneity between LDL-C and Lp(a) effects. 95 Concordance was defined as LDL-C reduction >35% and Lp(a) reduction >10%.…”
Section: Pcsk9 Inhibitors and Lp(a)mentioning
confidence: 99%